2018
DOI: 10.3389/fphar.2018.00111
|View full text |Cite
|
Sign up to set email alerts
|

Triple-Gene Therapy for Stroke: A Proof-of-Concept in Vivo Study in Rats

Abstract: Natural brain repair after stroke is extremely limited, and current therapeutic options are even more scarce with no clinical break-through in sight. Despite restricted regeneration in the central nervous system, we have previously proved that human umbilical cord blood mono-nuclear cells (UCB-MC) transduced with adenoviral vectors carrying genes encoding vascular endothelial growth factor (VEGF), glial cell-derived neurotrophic factor (GDNF), and neural cell adhesion molecule (NCAM) successfully rescued neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 53 publications
1
17
0
Order By: Relevance
“…An important factor is the absence of legal, ethical, and religious prohibitions related to blood cell transplantation. In our previous study, we showed that intrathecal injection of adenoviral vectors carrying vegf, gdnf, and ncam, or genetically-modified UCB-MC+Ad5-VEGF-GDNF-NCAM, 4 h after stroke modelling in rats, had a positive effect on the morpho-functional recovery of the post-ischemic brain [25]. Adenoviral vectors and genetically-modified UCB-MC with cerebrospinal fluid reached the ischemic area and delivered the production of recombinant VEGF, GDNF, and NCAM, lasting up to 21 days in the experiment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An important factor is the absence of legal, ethical, and religious prohibitions related to blood cell transplantation. In our previous study, we showed that intrathecal injection of adenoviral vectors carrying vegf, gdnf, and ncam, or genetically-modified UCB-MC+Ad5-VEGF-GDNF-NCAM, 4 h after stroke modelling in rats, had a positive effect on the morpho-functional recovery of the post-ischemic brain [25]. Adenoviral vectors and genetically-modified UCB-MC with cerebrospinal fluid reached the ischemic area and delivered the production of recombinant VEGF, GDNF, and NCAM, lasting up to 21 days in the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…The neuroprotective effect of these factors has been experimentally proven, but there is no unequivocal, let alone exhaustive, answer to the question of which of these factors may be recommended as neuroprotective factors in practical medicine. It has been established that combinations of several neurotrophic factors may have a more pronounced effect on nerve cell survival [25,28].…”
Section: Discussionmentioning
confidence: 99%
“…Results obtained by Sokolov et al imply that intrathecal injection of genetically engineered umbilical cord blood mononuclear cells (UCB-MC) over-expressing therapeutic molecules vascular endothelial growth factor (VEGF), glial cell line-derived neurotrophic factor (GDNF), neural cell adhesion molecule (NCAM) might represent a novel avenue for future research into treating stroke. Remodeling of the brain cortex in the stroke area was confirmed by the reduction of infarct volume and attenuated neural cell death, depletion of astrocytes and microglial cells, and an increase in the number of oligodendroglial cells and synaptic proteins expression [ 94 ].…”
Section: Gene Therapy For Strokementioning
confidence: 99%
“…The interactions between implanted hydrogel and endogenous brain cells have the potential to induce many different reparative and anti-inflammatory cellular pathways, through binding of CAPs (including RGD, IKVAV, and YISGR motifs) to specific cell surface receptors ( 101 ). Anti-inflammatory targets of CAPs include; cell adhesion molecules (CAMs), which are involved in the recruitment and trafficking of leukocytes ( 51 , 116 ); integrin receptors, which in addition to having anti-inflammatory effects can have proangiogenic properties ( 115 , 117 , 118 ), reduce reactive gliosis ( 43 , 119 ) and promote the infiltration of neural progenitor cells to the site of injury ( 43 , 111 ); and growth factor receptors that can initiate similar anti-inflammatory effects ( 120 ). CAPs can also be used to mimic growth factors and initiate preferential cellular pathways.…”
Section: Anti-inflammatory Strategies In Regenerative Medicinementioning
confidence: 99%
“…The use of gene therapies offers the potential to alter cellular and molecular processes that are important to recovery from ischemic stroke, reducing the inflammatory response and initiating regeneration of damaged tissue. This approach has been used to deliver anti-inflammatory gene therapies that promote production of VEGF ( 116 , 173 ), anti-inflammatory neural cell adhesion molecule (NCAM) ( 116 ), or IL-1Ra ( 50 ). These therapies were administered in rodents by intrathecal injection, but could be improved through encapsulation within a hydrogel for injection or implantation as this would control the release of gene-edited cells over time to increase the therapeutic effect.…”
Section: Anti-inflammatory Strategies In Regenerative Medicinementioning
confidence: 99%